Supraspinatus Tendon Changes and Glenohumeral Range of Motion in College Baseball Players - Ishigaki, Tomonobu; Hirokawa, Motoki; Ezawa, Yuya; Yamanaka, Masanori (International Journal of Sports Medicine, 2021)
Baseball players commonly show altered glenohumeral range of motion during internal rotation, external rotation, total rotation, and horizontal adduction. These altered ranges of motion appear to be associated with throwing shoulder injuries, which frequently involve the supraspinatus tendons; thus, we aimed to examine the relationship between altered glenohumeral range of motion and supraspinatus tendon changes in collegiate baseball players. To investigate this association using the Pearson correlation coefficient, we measured glenohumeral internal rotation, external rotation, total rotation, and horizontal adduction ranges of motion and supraspinatus tendon thickness in 22 college baseball players. Consequently, there was a significant relationship between increase in supraspinatus tendon thickness and greater deficit of internal rotation (r=–0.520, P=0.013). Increased supraspinatus tendon thickness tended to be associated with greater external rotation gain (r=0.394, P=0.073). No other range of motion had any relationship with supraspinatus tendon changes. These results might indicate that restricted glenohumeral internal rotation and excessive gain in external rotation increase the risk of supraspinatus tendon abnormalities in baseball players.